A perfect picture of hell : eyewitness accounts by Civil War prisoners from the 12th Iowa - Genoways, Ted; Genoways, Hugh H. (University of Iowa Press, 2001)
"From the shooting of an unarmed prisoner at Montgomery, Alabama, to a successful escape from Belle Isle, from the swelling floodwaters overtaking Cahaba Prison to the inferno that finally engulfed Andersonville, A Perfect Picture of Hell is a collection of harrowing narratives by soldiers from the 12th Iowa Infantry who survived imprisonment in the South during the Civil War." "Editors Ted Genoways and Hugh H. Genoways have collected the soldiers' startling accounts from diaries, letters, speeches, newspaper articles, and remembrances. Arranged chronologically, the eyewitness descriptions of the battles of Shiloh, Corinth, Jackson, and Tupelo, together with accompanying accounts of nearly every famous Confederate prison, create a shared vision of life in Civil War prisons as palpable and immediate as they are historically valuable. Captured four times during the course of the war, the 12th Iowa created narratives that reveal a picture of the changing southern prison system as the Confederacy grew ever weaker and illustrate the growing animosity many southerners felt for the Union soldiers."--Jacket